Study and Design Multiband MPA Antenna for Smart Phones - Fal, Jalal; AbuHamoud, Nassir; Abdulgader, Ali (Wadi Alshatti University Journal of Pure and Applied Sciences, 2026)
Modern wireless communication systems require compact multiband antennas that can operate efficiently over several frequency ranges used in mobile devices. However, conventional microstrip patch antennas often suffer from narrow bandwidth and limited gain, which restrict their use in multiband applications. This work presents the design and simulation of a compact slotted microstrip patch antenna intended for Wi-Fi, WLAN, WiMAX, and IMT applications. The antenna is designed on an FR-4 substrate and improved using rectangular slots and a partially reduced ground plane to enhance bandwidth and radiation characteristics. The proposed antenna is modeled and simulated using CST Microwave Studio 2019, and its performance is evaluated in terms of return loss, gain, directivity, VSWR, and surface current distribution. Simulation results show that the antenna operates effectively within the 2.9–7.6 GHz band, achieving resonant frequencies at 2.8 GHz, 3.80 GHz, and 4.61 GHz with a maximum bandwidth of 7.40 GHz. The design also provides a gain of up to 8.7 dB and maintains a VSWR below 2 across all operating bands. These results indicate that the proposed multiband slotted microstrip antenna is a strong candidate for integration into modern mobile and wireless communication systems.